Features of pain in patients with gunshot wounds depending on the location of injury at the stages of treatment - Iu.L. Kuchyn; V.R. Horoshko (Медицина неотложных состояний, 2023)
The incidence of gunshot wounds during the Anti-Terrorist Operation/Joint Force Operation is 54–70 %. More attention should be paid to the problem of pain treatment in patients with gunshot wounds, because about 70 % have negative treatment outcomes, which leads to pain chronicity. Chronic pain, in turn, is associated with several mutually aggravating factors — this can lead to the development of extremely serious long-term consequences. The features of pain in this category of patients have not been sufficiently studied. Taking into account continuity and consistency, clear and high-quality pain control is necessary at all stages of treatment.